PEMANFAATAN ASAP CAIR DALAM PENGENDALIAN TUMBUHAN MANTANGAN (Merremia peltata) SEBAGAI GULMA - M. Khalil Iqbal Lubis; M. Mardhiansyah Mardhiansyah; Sonia Somadona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Merremia peltata is a type of Invasive Allien Species (IAS) that belongs to one type of liana plants located in the tropics. Efforts to combat exgan for now are still very minimal because information about morphology and physiology of Merremia peltata is still lacking. The importance of this research is directed to develop an innovation in the control of exgan weeds by utilizing liquid smoke as a natural herbicide. This study aims to: (1) to find out the influence of liquid smoke as a natural herbicides in controlling the growth of Merremia peltata weeds; (2) to know the best dose of liquid smoke as a natural herbicide in controlling the growth of Merremia peltata. The study used the Complete Randomized Design (CRD) method which used five treatments and five repeats. Merremia peltata that has been grown for 14 days in 25 polybags 30x45 cm each polybag contains three Merremia peltata. After that spraying using grade 3 liquid smoke of various concentrations is carried out on the 15th day after planting. Spraying of grade 3 liquid smoke as much as 15 ml per polybag is carried out every two days until the 33rd day after planting. The data obtained was analyzed using fingerprint analysis test, if the real effect continued with Duncan's New Multiple Range Test (DNMRT) at a level of 5%. The data obtained and analyzed statistically using the SPSS application program. The results showed that the application of natural herbicides with grade 3 liquid smoke base material has an effect in suppressing the growth of Merremia peltata. Application of grade 3 liquid smoke with a dose of 15 ml / l is the most influential control and best in suppressing the growth of Merremia peltata as weeds Keywords : Merremia peltata, weed, liquid smoke, control, grade 3